HARGA SAHAM DENGAN METODE DIVIDEND DISCOUNT MODEL DAN PRICE TO BOOK VALUE - Resti Hasanah; Ellen Rusliati (Jurnal Riset Bisnis dan Manajemen, 2017)
This study aims to analyze the company’s intrinsic value using the dividend discount model (DDM) and price to book value (PBV) of companies registered in LQ 45, in 2010 - 2014. The sample selected by the criterion is always listed in the LQ 45 and pay dividends. The method used is descriptive and quantitative and the measurement accuracy with root mean squared error (RMSE). The results showed that intrinsic value DDM method is more accurate than PBV with an average value of DDM RMSE is smaller than the average RMSE PBV. DDM method is more suitable for companies with growth consistent and at the stage of maturity and always pay dividends. PBV method would be better to assess the company’s stock with similar industries or sectors, so the obvious comparison is cheap or expensive stocks.